Divergent Sensory Phenotypes in Nonspecific Arm Pain: Comparisons With Cervical Radiculopathy - Moloney, N.; Hall, Toby; Doody, C. (W.B. Saunders Co., 2015)
Objectives: To investigate whether distinct sensory phenotypes were identifiable in individuals with nonspecific arm pain (NSAP) and whether these differed from those in people with cervical radiculopathy. A secondary question considered whether the frequency of features of neuropathic pain, kinesiophobia, high pain ratings, hyperalgesia, and allodynia differed according to subgroups of sensory phenotypes. Design: Cross-sectional study. Setting: Higher education institution.Participants: Forty office workers with NSAP, 17 people with cervical radiculopathy, and 40 age- and sex-matched healthy controls (N=97). Interventions: Not applicable. Main Outcome Measures: Participants were assessed using quantitative sensory testing (QST) comprising thermal and vibration detection thresholds and thermal and pressure pain thresholds; clinical examination; and relevant questionnaires. Sensory phenotypes were identified for each individual in the patient groups using z-score transformation of the QST data. Results: Individuals with NSAP and cervical radiculopathy present with a spectrum of sensory abnormalities; a dominant sensory phenotype was not identifiable in individuals with NSAP. No distinct pattern between clinical features and questionnaire results across sensory phenotypes was identified in either group. Conclusions: When considering sensory phenotypes, neither individuals with NSAP nor individuals with cervical radiculopathy should be considered homogeneous. Therefore, people with either condition may warrant different intervention approaches according to their individual sensory phenotype. Issues relating to the clinical identification of sensory hypersensitivity and the validity of QST are highlighted.